ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII PADA MATERI BENTUK ALJABAR - Sakinah Oktaviani; Haerudin Haerudin (IKIP Siliwangi, 2021)
Learning mathematics by understanding mathematical concepts is very important, with students understanding mathematical concepts will help problems in mathematics, even problems in everyday life. This study aims to determine the ability to understand students' mathematical concepts in algebraic form material. This research uses qualitative research with descriptive method. The subjects in this study were seventh grade students in one of the junior high schools in Purwakarta Regency and the selection of subjects was done by purposive sampling technique. The data collection technique used is a description test of understanding mathematical concepts in algebraic form with 3 questions. The data were analyzed by giving a score for each subject's answer, then the recorded score was changed in the form of a percentage value. The test results were analyzed according to the indicators of the ability to understand concepts. It can be seen from the results of the research that the indicator restating a concept has a percentage of 64% with a good level of understanding, indicators using and choosing certain procedures or operations have a percentage of 53% with a sufficient level of understanding, and indicators of applying concepts or algorithms in problem solving have a percentage of 53% with a sufficient level of understanding. All students' ability to understand mathematical concepts has a percentage of 57% with a sufficient level of understanding.